2011
DOI: 10.1083/jcb.201009136
|View full text |Cite
|
Sign up to set email alerts
|

Heparan sulfate proteoglycan syndecan-3 is a novel receptor for GDNF, neurturin, and artemin

Abstract: Syndecan-3 may act alone or as a coreceptor with RET to promote cell spreading, neurite outgrowth, and migration of cortical neurons by GNDF, NRTN, and ARTN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
181
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(186 citation statements)
references
References 63 publications
2
181
1
2
Order By: Relevance
“…Thus, these cells would appear to be different from other MGE neurons in more aspects than just their expression of GFR1, which underlies a degree of diversity not previously appreciated in postmitotic GABAergic precursors of the MGE. While the present study was undergoing revision, Bespalov et al reported that the heparan sulfate proteoglycan syndecan-3 is able to bind GDNF and transmit GDNF signals independently of GFR1 (Bespalov et al, 2011). However, the effects of GDNF documented in our study are strictly dependent on GFR1, suggesting that they are not mediated by syndecan-3.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…Thus, these cells would appear to be different from other MGE neurons in more aspects than just their expression of GFR1, which underlies a degree of diversity not previously appreciated in postmitotic GABAergic precursors of the MGE. While the present study was undergoing revision, Bespalov et al reported that the heparan sulfate proteoglycan syndecan-3 is able to bind GDNF and transmit GDNF signals independently of GFR1 (Bespalov et al, 2011). However, the effects of GDNF documented in our study are strictly dependent on GFR1, suggesting that they are not mediated by syndecan-3.…”
Section: Discussioncontrasting
confidence: 50%
“…However, the effects of GDNF documented in our study are strictly dependent on GFR1, suggesting that they are not mediated by syndecan-3. Moreover, micromolar concentrations of GDNF were required to enhance neuronal migration through syndecan-3 (Bespalov et al, 2011), an amount that is several orders of magnitude greater than the one required for the effects reported in our study.…”
Section: Discussionmentioning
confidence: 78%
“…Interestingly, GDNF has also been shown to signal via a RET-independent mechanism (49), and the cellular effects of GFLs may, therefore, be propagated through multiple independent pathways. A recent report demonstrated that GDNF and ARTN also interact with SYNDECAN-3, a transmembrane heparin sulfate proteoglycan with subsequent activation of Src kinase (50). SYNDECAN-3 is expressed in myogenic stem cells and cooperates with Notch to promote cell cycle progression and self-renewal and inhibit terminal differentiation (51).…”
Section: Discussionmentioning
confidence: 99%
“…This cycle was repeated until we observed significant IRR (4 Gy) after assessing cell viability after IR treatment. The paclitaxel resistant cell lines were grown under selective pressure (IC 50 of each cell line) for 3 days and subsequently for 3 days without paclitaxel. This cycle was repeated until we observed significant paclitaxel resistance of paclitaxel-treated BT549 cells by assessing cell viability after paclitaxel treatment.…”
Section: Methodsmentioning
confidence: 99%
“…Although each GFL member binds one preferred GFRα receptor, there is a degree of promiscuity in their ligand specificities (Airaksinen et al, 1999;Ibanez and Andressoo, 2016;Paratcha and Ledda, 2008). In recent years, syndecan 3 has been described as a novel receptor for GFLs, although its functions do not appear to require GFRα1 (Bespalov et al, 2011). Interestingly, one of the members of the sortilin receptor family, SorLA (also known as SORL1), has recently been shown to be involved in the internalization and sorting of the GDNF-GFRα1 complex to the endosomal compartment (Glerup et al, 2013).…”
Section: Introductionmentioning
confidence: 99%